Digital Business Communication using TikTok Live Streaming - Herlina, Herlina; Rachmad, Teguh Hidayatul; Sasongko, Yohanes Probo Dwi (Yayasan Lentera Avanya Nagari, 2024)
TikTok live streaming allows broadcasters to share content in real time and interact with viewers through comments, emoticons, and other features. This research is a qualitative research using phenomenological techniques, where researchers analyze data scattered on the Internet and interviews with sources who have direct experience with TikTok live streaming. This research aims to find out the phenomenon of digital business communication using the TikTok live streaming platform. The results of the study concluded that 1) digital business communication using TikTok live streaming is an effective and efficient marketing medium in explaining product information in real time, which can attract viewers (consumers) to establish communication about the product, so it can influence consumer buying interest to make online purchases; 2) digital business communication using live streaming increases the level of consumer satisfaction with the quality of the products they buy; 3) digital business communication using live streaming can reduce the risk of fraud compared to digital businesses that only rely on photos, comments and videos; 4) live streaming digital business communication has the concept of traditional face-to-face communication, the difference is that if in traditional communication it is done face-to-face, live streaming communication in business is done in real-team and the audience can see the broadcaster's (seller's) gestures of the broadcaster (seller), while the seller only sees the audience (consumer) through comments, emoticons, and other features